Conductive silver paste for solar cell and solar cell
Patent Information
- Application Number
- CN202411506938.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The gate electrode bonding force of existing solar cells prepared by conductive silver paste is small, especially after aging, which cannot meet the requirements of the new technology.
A mixture of the first silver powder and the second silver powder is used. The first silver powder has an irregular structure polygonal plane. After grinding, it is mixed with the second silver powder with high spherical shape, and matched with specially prepared glass powder to form silver with good flatness. The silver powder melts during the sintering process and improves the bonding force between the silver layer and the layer to be connected.
The binding force of conductive silver powder is improved, and the binding force is maintained after the aging test, meeting the requirements of the new technology.
Smart Images

Figure CN119132694A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a conductive silver paste for solar cells and a solar cell. Background Art
[0002] Conductive silver paste is a key auxiliary material for preparing solar cells, and is mainly used to form the battery structure of the cell. In solar cells, the conductive silver paste is formed into a film through screen printing technology, and then sintered to form a grid electrode for collecting and conducting current on the surface of the cell. Silver powder is the conductive functional phase in the conductive silver paste, which directly affects the conductive performance.
[0003] At present, the gate electrode of solar cells prepared by conductive silver paste is prone to the problem of low bonding strength, and the bonding strength is even lower after aging, which can no longer meet the requirements of new technologies. Summary of the invention
[0004] Based on this, the first aspect of the present application provides a conductive silver paste for solar cells, and its technical solution is as follows:
[0005] A conductive silver paste, comprising silver powder, glass powder, an organic carrier, a solvent and an additive; the silver powder comprises a first silver powder and a second silver powder;
[0006] The primary particles of the first silver powder have an irregular structure, including a plurality of polygonal planes, and two adjacent polygonal planes intersect to form edges of the primary particles of the first silver powder;
[0007] The second silver powder is obtained by grinding the first silver powder;
[0008] The glass powder includes the following components in molar percentage:
[0009] Pb 3 O 4 6%~10%;
[0010] TeO 2 1%~5%;
[0011] Bi 2 O 3 20%~40%;
[0012] SiO 2 15%~25%;
[0013] Al 2 O 3 0.5%~1.5%;
[0014] B 2 O 3 20%~30%;
[0015] TiO 2 3%~8%;
[0016] ZnO5%~10%.
[0017] In some embodiments, the number of polygonal planes of the primary particles of the first silver powder is N, and 6≤N≤15.
[0018] In some embodiments, the side length of any polygonal plane of the primary particles of the first silver powder is in the range of 0.2 μm to 0.8 μm.
[0019] In some embodiments, the sphericity of primary particles of the first silver powder is 30% to 50%.
[0020] In some embodiments, the sphericity of primary particles of the second silver powder is 70% to 90%.
[0021] In some embodiments, the primary particle size of the first silver powder is in the range of 0.6 μm to 1.0 μm.
[0022] In some embodiments, the primary particle size of the second silver powder is in the range of 0.4 μm to 0.9 μm.
[0023] In some embodiments, the grinding method is jet milling.
[0024] In some embodiments, the first silver powder includes a first silver core and a first lauric acid layer covering the first silver core.
[0025] In some embodiments, the second silver powder includes a second silver core and a second lauric acid layer covering the second silver core.
[0026] In some embodiments, the mass ratio of the first silver powder to the second silver powder is 1:(0.3-3).
[0027] In some embodiments, the mass proportion of the silver powder in the conductive silver paste is 85% to 95%.
[0028] In some implementation methods, the glass powder accounts for 0.5% to 1.5% by mass in the conductive silver paste.
[0029] In some embodiments, the mass proportion of the organic carrier in the conductive silver paste is 1% to 7%.
[0030] In some embodiments, the organic carrier is selected from one or more of phenolic resin, silicone resin, epoxy resin, polyimide resin, polyurethane and acrylic resin.
[0031] In some embodiments, the mass percentage of the solvent in the conductive silver paste is 2% to 9%.
[0032] In some embodiments, the solvent is selected from one or more of tributyl citrate, diethylene glycol butyl ether acetate, isophorone and terpineol.
[0033] In some implementation methods, the mass proportion of the additive in the conductive silver paste is 0.5% to 1.5%.
[0034] In some embodiments, the auxiliary agent includes one or more of a toughening agent, a defoaming agent and a leveling agent.
[0035] In some embodiments, the toughening agent is selected from polyvinyl alcohol.
[0036] A second aspect of the present application provides a solar cell, which includes a gate electrode, wherein the gate electrode is prepared from the above-mentioned conductive silver paste.
[0037] Compared with the traditional solution, this application has the following beneficial effects:
[0038] The conductive silver paste of the present application uses a mixed powder of a first silver powder and a second silver powder, wherein the primary particles of the first silver powder include a plurality of polygonal planes with edges, and the second silver powder is obtained by grinding the first silver powder, and after grinding, the edges become more rounded and closer to a sphere. The mixing of the first silver powder and the second silver powder is conducive to the formation of a silver layer with good flatness, which produces better contact with the layer to be connected. At the same time, a specially formulated glass powder is used, which has a lower melting point. During the sintering process, it can promote the melting of the above-mentioned silver powder, make the silver layer denser, and improve the bonding strength between the silver layer and the layer to be connected. In summary, the present application is conducive to improving the bonding strength of the conductive silver powder, and after the aging test, it can still maintain a good bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0040] Figure 1 is the SEM image of the first silver powder;
[0041] Figure 2 is the SEM image of the second silver powder;
[0042] Figure 3 is the SEM image of the second silver powder;
[0043] Figure 4 This is the SEM image of the fourth silver powder. DETAILED DESCRIPTION
[0044] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0046] the term
[0047] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0048] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0049] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0050] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0051] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0052] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0053] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.
[0054] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0055] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.
[0056] Currently, the silver powder in conductive silver paste is mainly micron or submicron silver powder. The electrode binding force prepared by these conductive silver pastes is usually small, and the binding force is even lower after aging, which can no longer meet the requirements of new technologies.
[0057] The first aspect of the present application provides a conductive silver paste for solar cells. In one embodiment, the conductive silver paste comprises silver powder, glass powder, an organic carrier, a solvent and an additive; the silver powder comprises a first silver powder and a second silver powder;
[0058] The primary particles of the first silver powder have an irregular structure, including a plurality of polygonal planes, and two adjacent polygonal planes intersect to form edges of the primary particles of the first silver powder;
[0059] The second silver powder is obtained by grinding the first silver powder;
[0060] The glass powder includes the following molar percentages:
[0061] Pb 3 O 4 6%~10%;
[0062] TeO 2 1%~5%;
[0063] Bi 2 O 3 20%~40%;
[0064] SiO 2 15%~25%;
[0065] Al 2 O 3 0.5%~1.5%;
[0066] B 2 O 3 20%~30%;
[0067] TiO 2 3%~8%;
[0068] ZnO5%~10%.
[0069] The conductive silver paste of the present application uses a mixed powder of a first silver powder and a second silver powder, wherein the primary particles of the first silver powder include a plurality of polygonal planes with edges, and the second silver powder is obtained by grinding the first silver powder, and after grinding, the edges become more rounded and closer to a sphere. The mixing of the first silver powder and the second silver powder is conducive to the formation of a silver layer with good flatness, which produces better contact with the layer to be connected. At the same time, a specially formulated glass powder is used, which has a lower melting point. During the sintering process, it can promote the melting of the above-mentioned silver powder, make the silver layer denser, and increase the bonding tension between the silver layer and the layer to be connected. In summary, the present application is conducive to improving the bonding strength of the conductive silver powder, and after the aging test, it can still maintain a good bonding strength.
[0070] Optionally, the number of polygonal planes of the primary particles of the first silver powder is N, and 6≤N≤15. For example, the number N of polygonal planes of the primary particles of the first silver powder is 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15.
[0071] Optionally, the side length of any polygonal plane of the primary particles of the first silver powder is in the range of 0.2 μm to 0.8 μm. For example, the side length of any polygonal plane of the primary particles of the first silver powder is 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or 0.8 μm.
[0072] Optionally, the sphericity of the primary particles of the first silver powder is 30% to 50%. For example, the sphericity of the primary particles of the first silver powder is 30%, 40%, or 50%.
[0073] The longest distance between the two ends of the primary particle of the first silver powder is defined as the length, and the shortest distance between the two ends is the width. The number of particles with an aspect ratio between 1 and 5 accounts for no more than 5%, the number of particles with an aspect ratio between 1.5 and 2 accounts for 40% and 45%, the number of particles with an aspect ratio between 2 and 2.5 accounts for 30% and 35%, the number of particles with an aspect ratio between 2.5 and 3 accounts for 15% and 20%, and the number of particles with an aspect ratio between 3.5 and 4 accounts for no more than 5%.
[0074] Optionally, the particle size of the primary particles of the first silver powder is in the range of 0.6 μm to 1.0 μm. For example, the particle size of the primary particles of the first silver powder is 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, or 1.0 μm.
[0075] Optionally, the first silver powder includes a first silver core and a first lauric acid layer covering the first silver core. After being covered with the first lauric acid layer, it is beneficial to improve the tensile force and to ensure good tensile performance during and after the cooling process.
[0076] Optionally, the thickness of the first lauric acid layer is 0.02 μm to 0.08 μm. For example, the thickness of the first lauric acid layer is 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, or 0.08 μm.
[0077] Optionally, the grinding method is air jet milling.
[0078] Optionally, the process parameters of the jet mill are controlled so that the sphericity of the primary particles of the second silver powder is 70% to 90%, for example, the sphericity of the primary particles of the second silver powder is 70%, 80%, or 90%.
[0079] Optionally, the particle size of the primary particles of the second silver powder is in the range of 0.4 μm to 0.9 μm. For example, the particle size of the primary particles of the second silver powder is 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or 0.9 μm.
[0080] Optionally, the second silver powder includes a second silver core and a second lauric acid layer covering the second silver core. After being covered with the second lauric acid layer, it is beneficial to improve the tensile force and to ensure good tensile performance during and after the cooling process.
[0081] Optionally, the thickness of the second lauric acid layer is 0.02 μm to 0.08 μm. For example, the thickness of the second lauric acid layer is 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, or 0.08 μm.
[0082] The first silver powder can be commercially available.
[0083] Optionally, the mass ratio of the first silver powder particles to the second silver powder particles is 1:(0.3-3). For example, the mass ratio of the first silver powder particles to the second silver powder particles is 1:0.3, 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5, 1:3.
[0084] Optionally, the mass proportion of the silver powder in the conductive silver paste is 85% to 95%. For example, the mass proportion of the silver powder in the conductive silver paste is 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%.
[0085] Understandably, Pb 3 O 4 The molar percentage in the glass powder includes, but is not limited to, 6%, 7%, 8%, 9%, and 10%. 2 The molar percentage in the glass powder includes, but is not limited to, 1%, 2%, 3%, 4%, and 5%. 2 O 3 The molar percentage in the glass powder includes, but is not limited to, 20%, 25%, 30%, 35%, and 40%. SiO 2 The molar percentage in the glass powder includes, but is not limited to, 15%, 20%, and 25%. 2 O 3 The molar percentage in the glass powder includes, but is not limited to, 0.5%, 1%, and 1.5%. 2 O 3 The molar percentage in the glass powder includes, but is not limited to, 20%, 25%, and 30%. 2 The molar percentage in the glass powder includes, but is not limited to, 3%, 5%, and 8%. The molar percentage of ZnO in the glass powder includes, but is not limited to, 5%, 8%, and 10%.
[0086] Optionally, the glass powder does not include Cu and Mn elements, which is beneficial to improving the leveling property of the slurry, improving the bonding strength, and reducing the generation of fork marks.
[0087] Optionally, the glass powder accounts for 0.5% to 1.5% by mass in the conductive silver paste. For example, the glass powder accounts for 0.5%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, or 1.5% by mass in the conductive silver paste.
[0088] Optionally, the mass proportion of the organic carrier in the conductive silver paste is 1% to 7%. For example, the mass proportion of the binder in the conductive silver paste is 1%, 2%, 3%, 4%, 5%, 6%, or 7%.
[0089] Optionally, the organic carrier includes at least one of an organic binder and an inorganic binder, the organic binder is selected from one or more of phenolic resin, silicone resin, epoxy resin, polyimide resin, polyurethane and acrylic resin, and the inorganic binder includes glass powder.
[0090] Optionally, the mass proportion of the solvent in the conductive silver paste is 2% to 9%. For example, the mass proportion of the solvent in the conductive silver paste is 2%, 3%, 4%, 5%, 6%, 7%, 8%, or 9%.
[0091] Optionally, the solvent is selected from one or more of tributyl citrate, diethylene glycol butyl ether acetate, isophorone and terpineol.
[0092] Optionally, the mass proportion of the auxiliary agent in the conductive silver paste is 0.5% to 1.5%. For example, the mass proportion of the auxiliary agent in the conductive silver paste is 0.5%, 0.8%, 1%, 1.2%, or 1.5%.
[0093] Optionally, the auxiliary agent includes one or more of a toughening agent, a defoaming agent and a leveling agent.
[0094] Optionally, the toughening agent is selected from polyvinyl alcohol.
[0095] A second aspect of the present application provides a solar cell, which includes a gate electrode, wherein the gate electrode is prepared from the above-mentioned conductive silver paste.
[0096] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be sourced from commercial sources. The instruments used, unless otherwise specified, can all be sourced from commercial sources. The processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0097] Among them, the first silver powder is brand V18-X162B, purchased from Shenzhen Ha Shen Zhi Cai Co., Ltd., and the SEM picture is as follows Figure 1 As shown by Figure 1It can be seen that the primary particles of the first silver powder have an irregular structure, including multiple polygonal planes. The intersection of two adjacent polygonal planes constitutes the edge of the first silver powder particle. The number of polygonal planes is N, 6≤N≤10, and the side length of any polygonal plane is in the range of 0.2μm~0.8μm. The particle size of the primary particle is in the range of 0.6μm~1.0μm. The longest distance between the two ends of the primary particle of the first silver powder is defined as the length, and the shortest distance between the two ends is the width. The number of particles with an aspect ratio between 1 and 5 accounts for no more than 5%, the number of particles with an aspect ratio between 1.5 and 2 accounts for 40%~45%, the number of particles with an aspect ratio between 2 and 2.5 accounts for 30%~35%, the number of particles with an aspect ratio between 2.5 and 3 accounts for 15%~20%, and the number of particles with an aspect ratio between 3.5 and 4 accounts for no more than 5%. After testing, the sphericity of the first silver powder is 40%. The second silver powder is obtained by grinding the first silver powder particles, and the SEM image is as follows Figure 2 As shown by Figure 2 It can be seen that the particle size of one particle of the second silver powder is in the range of 0.4 μm to 0.9 μm. According to the test, the sphericity of the second silver powder is 80%, which shows that after the air flow milling, the sphericity of the second silver powder is higher.
[0098] The third silver powder is V19-X162A, purchased from Shenzhen Ha Shen Zhi Cai Co., Ltd., and the SEM image is as follows Figure 3 As shown by Figure 3 It can be seen that the third silver powder particles are spherical, and the primary particle size is in the range of 0.8 μm to 2 μm. According to the test, the sphericity of the second silver powder is 84%.
[0099] The fourth silver powder is V19-X262A, purchased from Shenzhen Ha Shen Zhi Cai Co., Ltd., and the SEM image is as follows: Figure 4 As shown by Figure 4 It can be seen that the fourth silver powder particles are spherical, and the primary particle size is in the range of 0.8 μm to 2 μm. According to the test, the sphericity of the second silver powder is 82%.
[0100] Example 1
[0101] This embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 8%,TeO 2 3%,Bi 2 O 3 29%, SiO 2 20%, Al 2O 3 1%, B 2 O 3 26%, TiO 2 5%, ZnO 8%.
[0102] Example 2
[0103] The present embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed, and stirred evenly to obtain a conductive silver paste, wherein the glass powder is the same as that in Example 1.
[0104] Example 3
[0105] The present embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed, and stirred evenly to obtain a conductive silver paste, wherein the glass powder is the same as that in Example 1.
[0106] Example 4
[0107] The present embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed, and stirred evenly to obtain a conductive silver paste, wherein the glass powder is the same as that in Example 1.
[0108] Example 5
[0109] The present embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed, and stirred evenly to obtain a conductive silver paste, wherein the glass powder is the same as that in Example 1.
[0110] Example 6
[0111] This embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 6%,TeO 2 4%,Bi 2 O 3 40%, SiO 2 15%, Al 2O 3 1%, B 2 O 3 24%, TiO 2 5%, ZnO 5%.
[0112] Example 7
[0113] This embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 7%, TeO 2 1%,Bi 2 O 3 27%, SiO 2 25%, Al 2 O 3 0.5%, B 2 O 3 30%, TiO 2 4.5%, ZnO 5%.
[0114] Example 8
[0115] This embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 10%, TeO 2 2%,Bi 2 O 3 22%, SiO 2 24%, Al 2 O 3 1.5%, B 2 O 3 27.5%, TiO 2 6%, ZnO 7%.
[0116] Example 9
[0117] This embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 49%,TeO 2 5%,Bi 2 O 3 32%, SiO 2 19%, Al 2 O 3 1%, B 2 O 3 20%, TiO 2 8%, ZnO 6%.
[0118] Example 10
[0119] This embodiment provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 8%,TeO 2 3%,Bi 2 O 3 20%, SiO 2 25%, Al 2 O 3 1.5%, B 2 O 3 29.5%, TiO 2 3%, ZnO 10%.
[0120] Comparative Example 1
[0121] This comparative example provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a third silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed, and stirred evenly to obtain a conductive silver paste, wherein the glass powder is the same as that in Example 1.
[0122] Comparative Example 2
[0123] This comparative example provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, the fourth silver powder, the second silver powder, the glass powder, the phenolic resin (organic carrier), the tributyl citrate (solvent) and the polyvinyl alcohol (auxiliary agent) are mixed, and stirred evenly to obtain the conductive silver paste, wherein the glass powder is the same as that in Example 1.
[0124] Comparative Example 3
[0125] The present comparative example provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 8%,TeO 2 3%,Bi 2 O 3 29%, SiO 2 20%, Al 2 O 3 1%, CuO 14%, MnO 2 12%, TiO 2 5%, ZnO 8%.
[0126] Comparative Example 4
[0127] The present comparative example provides a conductive silver paste, and the preparation method thereof is as follows: according to the mass ratio shown in Table 1, a first silver powder, a second silver powder, a glass powder, a phenolic resin (organic carrier), tributyl citrate (solvent) and polyvinyl alcohol (auxiliary agent) are mixed and stirred evenly to obtain a conductive silver paste, wherein the glass powder is composed of the following components in molar percentage: Pb 3 O 4 18%, TeO 2 3%,Bi 2 O 3 29%, SiO 2 15%, Al 2 O 3 1%, B 2 O 3 21%, TiO 2 5%, ZnO 8%.
[0128] Table 1
[0129]
[0130] test
[0131] Test Item 1: Print the conductive silver paste of each embodiment and comparative example onto the battery substrate, and form a gate electrode of the same circuit under the same sintering conditions. Solder the welding tape to the gate electrode, and pull the welding tape to test the tension between the gate electrode and the battery substrate. The results are shown in Table 2.
[0132] Test Item 2: Print the conductive silver paste of each embodiment and comparative example onto the battery substrate, and undergo the same sintering conditions to form a gate electrode with the same circuit. Age the gate electrode at 80°C for 3 hours, weld the welding tape to the gate electrode, and pull the welding tape to test the tension between the gate electrode and the battery substrate. The results are shown in Table 2.
[0133] Table 2
[0134]
[0135] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0136] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A conductive silver paste for solar cells, characterized in that: It includes silver powder, glass powder, organic carrier, solvent and additive; the silver powder includes first silver powder and second silver powder; The primary particles of the first silver powder have an irregular structure, including a plurality of polygonal planes, and two adjacent polygonal planes intersect to form edges of the primary particles of the first silver powder; The second silver powder is obtained by grinding the first silver powder; The glass powder includes the following components in molar percentage: Pb3O46%~10%; TeO21%~5%; Bi2O3 20%~40%; SiO215%~25%; Al2O30.5%~1.5%; B2O3 20%~30%; TiO23%~8%; ZnO5%~10%.
2. The conductive silver paste for solar cells according to claim 1, characterized in that: The number of polygonal planes of the primary particles of the first silver powder is N, and 6≤N≤15.
3. The conductive silver paste for solar cells according to claim 2, characterized in that: The side length of any polygonal plane of the primary particles of the first silver powder is in the range of 0.2 μm to 0.8 μm.
4. The conductive silver paste for solar cells according to claim 1, characterized in that: Includes at least one of the following features: (1) The sphericity of the primary particles of the first silver powder is 30% to 50%; (2) The sphericity of the primary particles of the second silver powder is 70% to 90%.
5. The conductive silver paste for solar cells according to claim 1, characterized in that: Includes at least one of the following features: (1) The primary particle size of the first silver powder is in the range of 0.6 μm to 1.0 μm; (2) The primary particle size of the second silver powder is in the range of 0.4 μm to 0.9 μm.
6. The conductive silver paste for solar cells according to any one of claims 1 to 5, characterized in that: The grinding method is air jet milling.
7. The conductive silver paste for solar cells according to any one of claims 1 to 5, characterized in that: Includes at least one of the following features: (1) The first silver powder includes a first silver core and a first lauric acid layer covering the first silver core; (2) The second silver powder includes a second silver core and a second lauric acid layer covering the second silver core.
8. The conductive silver paste for solar cells according to any one of claims 1 to 5, characterized in that: The mass ratio of the first silver powder to the second silver powder is 1:(0.3~3).
9. The conductive silver paste for solar cells according to any one of claims 1 to 5, characterized in that: Includes at least one of the following features: (1) The mass proportion of the silver powder in the conductive silver paste is 85% to 95%; (2) The mass proportion of the glass powder in the conductive silver paste is 0.5% to 1.5%; (3) The mass proportion of the organic carrier in the conductive silver paste is 1% to 7%; (4) The organic carrier is selected from one or more of phenolic resin, silicone resin, epoxy resin, polyimide resin, polyurethane and acrylic resin; (5) The mass proportion of the solvent in the conductive silver paste is 2% to 9%; (6) The solvent is selected from one or more of tributyl citrate, diethylene glycol butyl ether acetate, isophorone and terpineol; (7) The mass proportion of the additive in the conductive silver paste is 0.5% to 1.5%; (8) The auxiliary agent includes one or more of a toughening agent, a defoaming agent and a leveling agent.
10. A solar cell, characterized in that: It comprises a gate electrode, wherein the gate electrode is prepared from the conductive silver paste according to any one of claims 1 to 9.
Citation Information
Patent Citations
Surface-treated silver powder and preparation method therefor
CN111511489A
Low-silver single-printing front paste for solar cell and preparation method of low-silver single-printing front paste
CN117457254A
Conductive silver paste, preparation method thereof and solar cell
CN118039249A
Glass FRIT, and conductive paste composition and solar cell comprising the same
WO2013105812A1
Glass frit, preparation method therefor and electrode paste containing glass frit
WO2016169512A1
